Age of onset in health impact assessment of chemical substances. (14th May 2012) - Bokkers, Bas G.H.; Schuur, A. Gerlienke; Zeilmaker, Marco J.
The age at which a disability starts is important information when performing a quantitative health impact assessment of any particular chemical substance. From the fields of epidemiology and toxicology it is known that this age of onset may be influenced by chemical exposure and that this influence is dose (or exposure) dependent, i.e. effects will occur at younger ages when dose is increased. Approaches are suggested to obtain or estimate a decreased in age of onset related to chemical exposure. Dose–dependent age of onset information may be obtained from epidemiological and toxicological studies provided that these studies report time– and dose–response data in sufficient detail. In situations where such data are not available, assessing worst and best case situations could indicate the range of the health impact. It is suggested that the dose dependency of age of onset is accounted for in future health impact assessments of chemical substances.